Pengaruh Edukasi DAGUSIBU Obat terhadap Peningkatan Pengetahuan Kader PKK di Dusun Sanggrahan Desa Potronayan, Kecamatan Nogosari, Boyolali - Karuniawati, Hidayah; Salsabila, Aulia Shafa; Sikanaa, Arinaa Manaa; Saskia, Adinda Tri Prabandari; Dewi, Meilenia Shinta Kusuma; Hanjani, Wildanoor Sekar; Muhayaroh, Miftah (Abdi Geomedisains, 2024)
DAGUSIBU (DApatkan, GUnakan, SImpan, BUang) is a program initiated by pharmacists to improve the general community so that people can know how to get medicine, store, and dispose of drugs that are no longer used properly. The inappropriate use of drugs by the community is because of the lack of knowledge and information about the correct use of drugs. Therefore, efforts are needed to increase public knowledge through educational activities. This activity was conducted using the socialization method through counseling and distributing brochures containing knowledge about DAGUSIBU. Respondents filled out the questionnaire twice, namely before and after counseling. Data were analyzed descriptively and analytically with the Wilcoxon test because the data were not normally distributed. A total of 65 participants participated in this activity, with the age of the participants ranging from 21-60 years, the majority of education levels were Senior High School (SMA), as much as 45%, and 68% were homemakers. Statistical results showed a significant increase in knowledge between before and after counseling (p-value<0.05). So it can be concluded that counseling can increase appropriate knowledge about obtaining, using, storing, and disposing of drugs.